Open Government - Ramírez-Alujas, Álvaro (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This works analyzes the concept of corruption from different perspectives: law, economy, political science, ethics and sociology. It summarizes the different approaches and creates a typology. Finally, it gives an overview of the most important research challenges in this field.Open government is a new paradigm based on the principles of transparency and openness, participation and collaboration, that attempts to respond to the depletion of traditional models of governance in a world that is changing radically and rapidly. The paper develops a synthetic approach to the debate on the origin, scope and prospects of the concept and realizes its main components. On the other hand, it discusses the idea of understanding as a platform (open governance) for citizen participation and collaboration that encourages co-creation, co-design and co-management of public services, in a context where trust, co-responsibility and civic engagement are key to the process of change experienced by governments and public administrations faced the challenges imposed by society in the new millennium.